Membrane ectopeptidases targeted by human coronaviruses - Bosch, Berend Jan (Elsevier B.V., 2014)
Six coronaviruses, including the recently identified Middle East respiratory syndrome coronavirus, are known to target the human respiratory tract causing mild to severe disease. Their interaction with receptors expressed on cells located in the respiratory tract is an essential first step in the infection. Thus far three membrane ectopeptidases, dipeptidyl peptidase 4 (DPP4), angiotensin-converting enzyme 2 (ACE2) and aminopeptidase N (APN), have been identified as entry receptors for four human-infecting coronaviruses. Although the catalytic activity of the ACE2, APN, and DPP4 peptidases is not required for virus entry, co-expression of other host proteases allows efficient viral entry. In addition, evolutionary conservation of these receptors may permit interspecies transmissions. Because of the physiological function of these peptidase systems, pathogenic host responses may be potentially amplified and cause acute respiratory distress.